TINJAUAN YURIDIS PENYALAHGUNAAN ASET PROPERTI TANAH DAN BANGUNAN PT PLN (PERSERO) UNIT INDUK DISTRIBUSI JAWA TIMUR - Mohammad Adam Jourdan; Abraham Ferry Rosando (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Fixed assets are very important for a company. Many companies still consider the utilization of fixed assets as just an instrument for managing asset lists. Reality on the ground shows that many cases actually started with mismanagement and mismanagement of asset problems, resulting in significant losses. The formulation of the problem proposed by the author is how the pattern of securing property assets in the form of official homes at PT PLN's Distribution Main Unit in East Java is and how the legal remedies of PT PLN's East Java Distribution Main Unit are against misused assets. The research conducted by the author uses empirical legal research where empirical juridical legal research uses the rule of law, by means of legal research that examines the workings of law in society in this study. The result of the discussion is that the pattern of securing property assets of PT PLN East Java Distribution Parent Unit is as in Government Regulation No. 27 of 2014 concerning Management of Regional Property, there are several ways of securing assets including administrative aspects, physical aspects, legal aspects and aspects of utilization and legal remedies for PT. PLN is related to the misuse of official house property assets, namely controlling assets internally and if it is not biased, a subpoena is carried out by the High Prosecutor's Office